STUDI KELAYAKAN ISI BUKU ILMU PENGETAHUAN ALAM KELAS IV MADRASAH IBTIDAIYAH DARI KEMENTRIAN PENDIDIKAN - Anisa Wardatuldiniah; Abdur Rahim (JOEL: Journal of Educational and Language Research, 2022)
Content feasibility is one of the four eligibility criteria for a textbook to consider based on regulations from the National Education Standards Agency (BSNP) in Indonesia. Textbooks are always the main source or reference for information or knowledge retrieval. Therefore, the feasibility of a textbook is very important. Based on this the problem formulation compiled, namely (1) How is the feasibility of the contents contained in the Electronic School Book (BSE) of Natural Sciences Class IV SD/ MI Published by Ministry of National Education based on Core Competencies and Basic Competencies? and (2) What is the appropriateness of the contents contained in the Electronic School Book (BSE) of Natural Sciences Class IV SD / MI Published by Ministry of National Education based on the accuracy of the material?. This research is a library research with analysis approach. The data collection techniques were documentation and technical analysis of the data or content. This means, the researcher conducted an analysis of the material or content contained in primary data (textbooks). The results showed that (1) Electronic School Book of Natural Sciences Class IV SD / MI Published by the Ministry of National Education is feasible based on the results of the feasibility study with a value of 75.71%. However, the Core Competencies and Basic Competencies still need to be developed in accordance with the 2013 Curriculum Revised 2018 to keep abreast of the times; (2) For the accuracy of the material in the Electronic School Book of Natural Sciences Class IV SD / MI Published by the Ministry of National Education is feasible it only lacks with the latest features in completing examples.